Re-imagining the role of protected areas in the social-ecological landscape: connecting people to nature through water-related ecosystem services - Smith, Janis Suzanne (Stellenbosch : Stellenbosch University, 2025)
Thesis (PhD)--Stellenbosch University, 2025.